SC11 The impact of video vs oral debrief on experiential learning and skills transference; an action research study. (3rd November 2019) - Toft, Lisa
Abstract : Background: Portsmouth Hospitals Simulation Centre is located in a busy district general hospital, employing over 7, 000 staff. The centre recently upgraded its audio-visual equipment, creating opportunities to introduce video debrief into practice. Project: As part of an on going Master's Dissertation, a qualitative action research study will be carried out in July and August 2019, exploring the use of video debrief in comparison to oral debrief when applied to a session for newly employed overseas nurses, as part of a transition programme. Literature supporting the use of video debriefing compared with oral found minimal evidence to support either method was superior. A study from Ostovar et al (2018) concluded that although improvements had been seen in specific skills and confidence, there was no evidence that oral verses video debrief was superior over another. Despite the evidence, the exploration of video debrief is available for educators to enhance specific scenarios or courses. The aim of the study is to: Analyse how video debrief and tradition oral debrief supports the reflection and analysis of events through experiential learning. A Comparison of the exploration of technical and non –technical skills between two different debrief approaches, against the learning objectives. Evaluation of the transference of knowledge and skills learned in simulation to real practice. The study participants will be separated into 2 control groups; oral and video debrief. Each group will undertake the same 3 scenarios, either as participant or observer during the simulation. All the candidates will complete a semi-structured qualitative questionnaire, reflecting on the key skills taken from the session and experience of debrief. Zigmont et al (2011) describes the use of simulation as a method to allow learners to move from comprehension to application, analysis and synthesis, which can be an indicator of competence in practice. A follow up semi-structures qualitative questionnaire will be sent 4 weeks post training to explore the skills transference to practice, as part of the experiential learning cycle. A thematic analysis will be completed in August 2019, analysing the reflection when compared to each debrief with conclusions and recommendations being drawn. Reference: Ostovar S., Allahbakhshian A., Gholizadeh L., Dizaji, S.L., Ghahramanian A. (2018) Comparison of the effects of debriefing on psychomotor skills, self-confidence and satisfaction in novice nursing students: a quasi-experimental study. Journal of Advanced Pharmaceutical Technology and Research, 9, 107–112. Zigmont J.J., Kappus L.J., Sudikoff S.N. (2011) Theoretical foundations of learning through simulation. Seminars and Perinatology, 35(2) 47–51. doi: 10.1053/j.semperi.2011.01.002.